2022
DOI: 10.3389/fphar.2022.833066
|View full text |Cite
|
Sign up to set email alerts
|

Protective Signature of IFNγ-Stimulated Microglia Relies on miR-124-3p Regulation From the Secretome Released by Mutant APP Swedish Neuronal Cells

Abstract: Microglia-associated inflammation and miRNA dysregulation are key players in Alzheimer’s disease (AD) pathophysiology. Previously, we showed miR-124 upregulation in APP Swedish SH-SY5Y (SWE) and PSEN1 iPSC-derived neurons and its propagation by the secretome (soluble and exosomal fractions). After modulation with miR-124 mimic/inhibitor, we identified common responsive mechanisms between such models. We also reported miR-124 colocalization with microglia in AD patient hippocampi. Herein, we determined how miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 113 publications
(184 reference statements)
1
23
0
Order By: Relevance
“…In our prior studies, we demonstrated that miR-124 levels in the secretome recapitulate the levels observed in cells, either non-modulated or treated with its mimics and inhibitors [ 9 , 10 , 11 , 13 ]. Here, we intended to test whether the intrathecal injection of the secretome from anti-miR-124 mSOD1 MNs in pre-symptomatic mSOD1 mice was able to reduce the miR-124 expression in the lumbar SC of ALS mice when assessed at 15 weeks of age.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In our prior studies, we demonstrated that miR-124 levels in the secretome recapitulate the levels observed in cells, either non-modulated or treated with its mimics and inhibitors [ 9 , 10 , 11 , 13 ]. Here, we intended to test whether the intrathecal injection of the secretome from anti-miR-124 mSOD1 MNs in pre-symptomatic mSOD1 mice was able to reduce the miR-124 expression in the lumbar SC of ALS mice when assessed at 15 weeks of age.…”
Section: Resultsmentioning
confidence: 97%
“…miR-124 is the most abundant miRNA in the adult brain and has been described as a regulator of microglia-mediated inflammation in neurological diseases [ 10 , 60 ]. It is mainly expressed in neuronal cells, showing important functions in neuronal development, differentiation, synaptic plasticity, and even in memory signalling molecules [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes can regulate synaptic plasticity through microglia. Studies have shown that exosomes can regulate neuroplasticity (Xin et al, 2013 ) and neuronal development and maintain myelin and synaptic function in peripheral brain infarcts by enhancing neurite remodeling (Domingues et al, 2020 ), thus affecting the morphology and function of microglia (Vogel et al, 2018 ; Garcia et al, 2022 ) and the density of dendritic spines (Sobue et al, 2018 ). Combined with our previous studies, we speculate that exercise can regulate synaptic plasticity by inhibiting the excessive activation of microglia after exosomes enter the brain.…”
Section: Discussionmentioning
confidence: 99%